PENERAPAN DIGITAL MARKETING DALAM MEMBANGUN CITRA MEREK PADA SAGA CREATIVE HUB SEBAGAI PUSAT EKONOMI KREATIF - Yana Diana; Vina Arnita (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Advances in digital technology are encouraging players in the creative economy to adopt more effective and sustainable marketing strategies. This study aims to analyse the role of digital marketing strategies in building the image of Saga Creative Hub as a hub for the creative economy. The method used in this study is a qualitative descriptive approach, with data collected through observation, interviews and documentation of the digital promotional activities carried out by Saga Creative Hub. The results of the study indicate that the use of social media, particularly Instagram, the consistent creation of creative content, and well-planned digital communication are capable of increasing brand awareness, audience engagement, and strengthening the image of Saga Creative Hub as a space for collaboration and innovation. Digital marketing strategies also contribute to expanding the creative community network and enhancing appeal for MSME practitioners and the general public. The conclusion of this study emphasises that the implementation of appropriate and sustainable digital marketing strategies plays a strategic role in building the image of creative economy institutions. It is hoped that this study will serve as a reference for creative hub managers and creative economy practitioners in developing effective digital promotion strategies. Keywords: digital marketing, brand image, creative economy, creative hub, social media   Abstrak: Perkembangan teknologi digital mendorong pelaku ekonomi kreatif untuk mengadaptasi strategi pemasaran yang lebih efektif dan berkelanjutan. Penelitian ini bertujuan untuk menganalisis peran strategi digital marketing dalam membangun citra Saga Creative Hub sebagai pusat ekonomi kreatif. Metode yang digunakan dalam penelitian ini adalah pendekatan deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi terhadap aktivitas promosi digital yang dilakukan oleh Saga Creative Hub. Hasil penelitian menunjukkan bahwa pemanfaatan media sosial, khususnya Instagram, pembuatan konten kreatif yang konsisten, serta komunikasi digital yang terencana mampu meningkatkan brand awareness, engagement audiens, dan memperkuat citra Saga Creative Hub sebagai ruang kolaborasi dan inovasi. Strategi digital marketing juga berkontribusi dalam memperluas jejaring komunitas kreatif serta meningkatkan daya tarik bagi pelaku UMKM dan masyarakat. Kesimpulan dari penelitian ini menegaskan bahwa implementasi strategi digital marketing yang tepat dan berkesinambungan memiliki peran strategis dalam membangun citra lembaga ekonomi kreatif. Penelitian ini diharapkan dapat menjadi referensi bagi pengelola creative hub dan pelaku ekonomi kreatif dalam mengembangkan strategi promosi digital yang efektif. Kata Kunci: digital marketing, citra merek, ekonomi kreatif, creative hub, media sosial